Changes in oxidative stress and acid-base balance in men and women following maximal-intensity physical exercise - Wiecek, M; Maciejczyk, M; Szymura, J; Szygula, Z (Physiological research, 2015)
Oxidative stress may be caused by an increased rate of ATP resynthesis during physical exercise. The aim of this study was to compare changes in the prooxidant-antioxidant state of blood plasma between men and women after maximal-intensity exercise, and to assess the relationship between these changes and the value of the maximal oxygen uptake (VO(2max)) as well as between these changes and the value of post-exercise disruptions in acid-base balance. Study participants comprised 10 women (20.7 ± 0.5 years) and 10 men (22.3 ± 0.5 years) who were physically active but did not engage in competitive sports training. VO(2max) was determined via treadmill incremental test (VO(2max) relative to body mass: 44.48 ± 1.21 ml/kg/min and 59.16 ± 1.55 ml/kg/min for women and men, respectively). The level of acid-base balance indicators (ABB), lactate concentration (La⁻), the level of total oxidative status (TOS), the level of total antioxidative capacity (TAC), and uric acid (UA) concentration were measured before and after the test. An oxidative stress indicator (OSI) was also calculated. Men showed a significant post-exercise increase in the level of TOS and OSI, while women showed a significant post-exercise increase in the level of TAC. Post-exercise changes in UA concentration were insignificant. Post-exercise changes in TOC in men depended on the absolute values of VO(2max), on VO(2max)/LBM, and on post-exercise changes in La⁻ concentration.
Keywords: kyselina močová; Antioxidants; Female; biologické markery; oxidační stres; Hydrogen-Ion Concentration; Biomarkers; mladý dospělý; ženské pohlaví; Lactic Acid; kyselina mléčná; Oxidative Stress; Time Factors; časové faktory; Oxygen Consumption; běh; lidé; cvičení; fyziologická adaptace; Running; Sex Factors; Male; sexuální faktory; Young Adult; antioxidancia; Adaptation, Physiological; Acid-Base Equilibrium; mužské pohlaví; acidobazická rovnováha; Exercise; koncentrace vodíkových iontů; Uric Acid; spotřeba kyslíku; Humans